Quality Culture Model in Improving Development Madrasah Universitas Islam Negeri Jakarta Indonesia and Ma'had Al Ulum Addiniyah Thailand - Masyitoh, Masyitoh; Bahar, Herwina; Suryadi, Ahmad; Bahri, Saiful; Nisoh, Anan; Niwae, Yahaya; Sama-alee, Abdulrahman; Sundi, Venni Herli (EDUPEDIA Publisher, 2023)
The purpose of this research is to compare the quality culture of Islamic Education Institutions in Indonesia and in Thailand, specifically the UIN Jakarta Development Madrasah and Ma'had Al-Ulum Addiniyah Pohontanjong Narathiwat with the eight National Education Standards (SPN). This research method is descriptive-comparative with a qualitative approach. The results showed the characteristics of the quality culture of each Islamic Education Institution in Indonesia and in Thailand, in addition to the similarities in the management of these Educational Institutions such as, the characteristics of the quality culture of the UIN Jakarta Development Madrasah and the characteristics of the quality culture of Ma